Methods for Evaluating New Product Designs in the Portfolio Management Process in the Pre‑Market Phases of Product Life Cycle - Rutkowski, Ireneusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The goal of the paper is to present methods for evaluating new product designs or projects in an integrated new product development process, as well as to propose a new method for optimising the value of new product portfolio management (NPPM) in the pre market phases of product life cycle. The success level of a new product development strategy is significantly dependent on the degree of a company’s competence, firstly in the implementation of the new product development process (NPDP), and secondly in the proper evaluation and selection of new product design concepts (executing the right project). In particular, the latter area of competence is related to the issues of portfolio management in the field of new product development. Thus, we are dealing here with a dynamic decision making process – the Stage Gate Process, according to which the design team is constantly updating, implementing and revising the current set of new product designs. Strategic decisions are also made on the allocation or reallocation of resources between active projects and whether to accelerate their implementation, change the assigned priority or abandon the project. This is a conceptual and methodological paper based on strategic management concepts and applications. It relates to new product development research. Methodological and research limitations identified in this work result from such circumstances as time and financial constraints or information availability. The scientific result of the article is a modified rank resource method of evaluating projects/programmes in the NPDP funnel (a portfolio of projects at individual stages and gates of development process), containing both qualitative and quantitative criteria.